Case of pembrolizumab-induced myocarditis presenting as torsades de pointes with safe re-challenge. (September 2020) - Lee, Dae Hyun; Armanious, Merna; Huang, Jessica; Jeong, Daniel; Druta, Mihaela; Fradley, Michael G
Introduction: Pembrolizumab is an immune checkpoint inhibitor targeting the programmed death receptor with clinical effect on multiple malignancies including sarcoma. Associated cardio-toxicities include myocarditis, cardiomyopathy, heart failure, and arrhythmias. Although in most cases of immune checkpoint inhibitor cardiotoxicity the offending agent is discontinued, we report a case of successful and safe re-challenge with a checkpoint inhibitor in a patient with mild myocarditis. Case report: We describe a 37-year-old female with alveolar soft part sarcoma, metastatic to the lungs on cycle 13 of pembrolizumab who presented with dyspnea, cough, and vague chest discomfort. Telemetry showed bigeminal bradycardia that transitioned to self-terminating torsades de pointes. Cardiac MRI showed subtle patchy T2 signal increase within the left ventricular septum without late gadolinium uptake, suggesting mild focal myocarditis. Management and outcome: The patient was started on a steroid taper without additional arrhythmias. We have re-challenged the patient who safely tolerated re-challenge with pembrolizumab despite an episode of torsades de pointes and documented myocarditis. She continues to receive pembrolizumab at seven months after the initial event without further cardiovascular events. Discussion: To the best of our knowledge, this is the first reported case of successful re-challenge of pembrolizumab after an episode of myocarditis. In patients with mild myocarditis and no evidence of left ventricular dysfunction, re-challenge may be a viable option. However, close monitoring for the development of heart failure, cardiomyopathy, or serious arrhythmias is necessary to ensure patient safety.